Association Between Coping Strategies and Psychological Well-Being among Urban Adolescents in an Islamic Senior High School - Sri Angriani; Rahman Rahman; Abd. Hady; Rusni Mato (Direktorat Politeknik Kesehatan Makassar, 2026)
Adolescence is a developmental stage characterized by academic, social, and emotional challenges that may influence psychological well-being. Coping strategies are considered important factors that help adolescents manage stress and maintain positive psychological functioning. This study aimed to examine the association between coping strategies and psychological well-being among adolescents. This study employed a quantitative descriptive–correlational design with a cross-sectional approach. The research was conducted at a religious-based senior high school in Makassar, Indonesia, involving 36 adolescents selected using stratified random sampling. Coping strategies were measured using the Brief COPE questionnaire, while psychological well-being was assessed using an adapted Psychological Well-Being (PWB) questionnaire. Both variables were categorized into categorical data for bivariate analysis purposes. Data were analyzed using descriptive statistics and Chi-square analysis to examine the association between coping strategy categories and psychological well-being levels. Because of the relatively small sample size, the findings were interpreted cautiously. Most respondents demonstrated adaptive coping strategies (94.4%) and high psychological well-being (61.1%). Statistical analysis showed that coping strategies were significantly associated with psychological well-being (p < 0.05), indicating that adolescents who applied adaptive coping strategies tended to demonstrate higher psychological well-being. However, findings related to maladaptive coping should be interpreted cautiously because the number of respondents in this category was very limited. Adaptive coping strategies were positively associated with psychological well-being among adolescents. These findings highlight the importance of strengthening adaptive coping skills through school-based mental health programs. Future studies are recommended to involve larger and more diverse populations to improve generalizability.